Hidden Histories of Gender and the State in Latin America - Molyneux, Maxine; Dore, Elizabeth (Book collections on Project MUSE., 2000)
This collection examines the mutually influential interactions of gender and the state in Latin America from the late colonial period to the end of the twentieth century. Locating watershed moments in the processes of gender construction by the organized power of the ruling classes and in the processes by which gender has conditioned state-making, Hidden Histories of Gender and the State in Latin Americaremedies the lack of such considerations in previous studies of state formation. Along these lines, the book begins with two theoretical chapters by the editors, Elizabeth Dore and Maxine Molyneux. Dore opens by arguing against the prevailing view that the nineteenth century was marked by a gradual emancipation of women, while Molyneux considers how various Latin American state formsliberal, corporatist, socialist, neoliberalhave more recently sought to incorporate women into their projects of social reform and modernization. These essays are followed by twelve case studies that examine how states have contributed to the normalization of male and female roles and relations. Covering an impressive breadth not only of historical time but also of geographical scope, this volume moves from Brazil to Costa Rica, from Mexico to Chile, traversing many countries in between. Contributors explore such topics as civic ritual in Bolivia, rape in war-torn Colombia, and the legal construction of patriarchy in Argentina. They examine the public regulation of domestic life, feminist lobby groups, class compromise, female slaves, and women in rural householdsdistinct, salient aspects of the state-gender relationship in specific countries at specific historical junctures. By providing a richly descriptive and theoretically grounded account of the interaction between state and gender politics in Latin America, this volume contributes to an important conversation between feminists interested in the state and political scientists interested in gender. It will be valuable to such disciplines as history, sociology, international comparative studies, and Latin American studies. Contributors. María Eugenia Chaves, Elizabeth Dore, Rebecca Earle, Jo Fisher, Laura Gotkowitz, Donna J. Guy, Fiona Macaulay, Maxine Molyneux, Eugenia Rodriguez, Karin Alejandra Rosemblatt, Ann Varley, Mary Kay Vaughan.